The Effect of Blend Fuel Waste Plastic and Waste Cooking Oil on Diesel Engine Performance based on Simulation - Aguk Zuhdi M. Fathallah; Adhi Iswantoro; A Karomur Roziq F (Institut Teknologi Sepuluh Nopember, 2020)
Nowadays, polypropylene plastics are very often found and cause various environmental problems. Though it is known that along with polypropylene itself comes from propylene monomers obtained from refining petroleum. Besides the use of waste cooking, biodiesel fuel has many drawbacks, one of which is power and fuel consumption. Mixing polypropylene plastic waste for reuse with waste cooking oil biodiesel is an option. This study uses five variations of fuel, namely HSD, B30, C20, C30, and C40, a combination of HSD, waste cooking, and polypropylene. This research is based on experiments to analyze the impact of using these five variations of fuel on the performance diesel engines based on simulation. The performance of the diesel engine would be measured to SFOC, power, and torque produced by each fuel. Based on the results of the analysis of the performance of the diesel engine performance of C20, fuel can be the most optimum alternative fuel to the substitute B30, producing 6.0 kW of power, 238gr / kWh of SFOC, and 31.7Nm of torque.